Persistent Hydrodynamic Cues Elicit Orientation-Specific Behavioral Sensitivities and Kinematic Responses in Dispersed Crab Larvae - True, Aaron C.; Webster, Donald R.; Weissburg, Marc J.; Yen, Jeannette (Frontiers in Marine Science, 2020)
The estuarine mud crab Panopeus herbstii navigates a complex, but structured, hydrodynamic environment throughout its life history. The effects of hydrodynamic cues associated with turbulent flows on larval behavior are relatively well understood in the context of selective tidal stream transport (STST) phenomena during the dispersed (pelagic) larval stages preceding benthic settlement. In contrast, the potential relevance of hydrodynamic cues associated with spatiotemporally persistent flow features, which are typical of estuarine regions of enhanced productivity such as fronts and clines, remains much less certain. To investigate the behavioral relevance of persistent hydrodynamic cues, larval assays were conducted in a flume system that uses a laminar slot jet to produce steady fluid shear layers. Further, to ascertain whether or not the spatial orientation of the shear layers relative to gravity significantly affected larval behavior, assays were conducted in upwelling, downwelling, and horizontal shear flows, corresponding to the direction of the bulk flow produced by the jet. The flow was quantified using particle image velocimetry (PIV) and tuned to produce ecologically-relevant hydrodynamic conditions for larval assays. Changes in larval swimming kinematics show a distinct response to shear flows in all orientations relative to no-flow conditions, and the macro effect of these changes is to enhance depth-keeping and induce area-restricted search behaviors. Furthermore, the specifics of larval behavioral responses depend on the directional orientation of the shear flow, and the statistical properties of the strength of the hydrodynamic cue (vorticity) eliciting these responses are also shown to be shear flow orientation-specific. Orientation-specific hydrodynamic sensitivity and behavioral response strategies in the presence of persistent hydrodynamic cues may enable larvae to effectively forage and sample to locate and exploit nearby resource patches, while also inducing dispersal trajectories towards favorable benthic settlement habitats through depth regulation and effective STST. In this regard, hydrodynamic cues associated with spatiotemporally persistent flow features are likely fundamental drivers of decapod crab larvae behavior and may act as another mechanism of larval patchiness by directly impacting finescale population distributions and resultant dispersal trajectories.